Renaissance & reformation: German art in the age of Dürer and Cranach - Plackinger, Andreas; Eissenhauer, Michael; Syndram, Dirk; Maaz, Bernhard; Smith, Jeffrey Chipps; Chapuis, Julien (Prestel, 2016)
Directors' forewords / Michael Govan ... [et al.] -- Essays. The Staatliche Museen zu Berlin : one museum, many sites, one mission / Michael Eissenhauer. The Staatliche Kunstsammlungen Dresden : from electoral art chamber to universal museum / Dirk Syndram. The Bayerische Staatsgemäldesammlungen München : half a millenium of painting / Bernhard Maaz. German art in the sixteenth century : an introduction / Jeffrey Chipps Smith -- Catalogue. Traditional imagery and devotion ; Reformation and polemics ; Court and culture ; Humanism and reality ; Portraiture and status -- Appendix. Artists' biographies ; Glossary of the Reformation